2012
DOI: 10.1007/s10618-012-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of extreme events-related communities in contrasting groups of physical system networks

Abstract: The latent behavior of a physical system that can exhibit extreme events such as hurricanes or rainfalls, is complex. Recently, a very promising means for studying complex systems has emerged through the concept of complex networks. Networks representing relationships between individual objects usually exhibit community dynamics. Conventional community detection methods mainly focus on either mining frequent subgraphs in a network or detecting stable communities in time-varying networks. In this paper, we form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The results obtained from big data analytics can provide a stronger decision-making power, a deeper discovery power, a more optimal procedure power, and a more precise analysis power at the same time [42]. However, when employing big data analytics, big data with characteristics of volume, velocity, variety and veracity must be satisfied, and a research methodology including analytic visualizations, data mining algorithm, predictive analytic capabilities, semantic engines, and data quality and master data management must be considered [43]. In addition, overall handling procedures consisting of data collection, preprocess, statistics and analysis, and data mining must be carefully processed [42].…”
Section: In Thementioning
confidence: 99%
“…The results obtained from big data analytics can provide a stronger decision-making power, a deeper discovery power, a more optimal procedure power, and a more precise analysis power at the same time [42]. However, when employing big data analytics, big data with characteristics of volume, velocity, variety and veracity must be satisfied, and a research methodology including analytic visualizations, data mining algorithm, predictive analytic capabilities, semantic engines, and data quality and master data management must be considered [43]. In addition, overall handling procedures consisting of data collection, preprocess, statistics and analysis, and data mining must be carefully processed [42].…”
Section: In Thementioning
confidence: 99%
“…the occurrence of multiple operating "phases" of a system, with feedback loops existing between these phases. In [9], the authors have attempted to identified the occurrence of "anomalous" communities in such phased-based systems. Another perspective is taken by Rahwan et al [11], where they consider how "social mobilisation" could be used to enable the detection of rare events (considered in the context of the DARPA "Network Challenge" [12] and the subsequent "Tag Challenge").…”
Section: Related Workmentioning
confidence: 99%
“…For instance, the machine learning algorithms [2,3,17] have been specifically designed to overcome underdetermined problem spaces when performing classification. While they are largely successful in their test applications, their predictions do not take advantage of hierarchical characteristics such as system-subsystem relationships, nor are the prediction results checked against these characteristics for sanity.…”
Section: Motivating Examplementioning
confidence: 99%
“…Classification has been extensively studied in various domains, including extreme event prediction [3,4], text classification [12], and sentiment analysis [13], etc. To the best of our knowledge, this paper is the first work addressing the detection and correction of potential errors in prediction results of a multi-class classification algorithm.…”
Section: Related Workmentioning
confidence: 99%